STUDYING OF THE USE OF BASALT MINERALS AS A POLYETHYLENE FILLER AND ITS PHYSICOCHEMICAL PROPERTIES (Journal of Universal Science Research, 2023)
In this article, a study of the use of basalt minerals as a polyethylene filler was conducted. According to the obtained results, basalt fibers and basalt fabrics were extracted from basalt minerals and applied to basalt in the amount of 30%. The composition of the composite was studied and analyzed using IR spectra.